Machinability exploration for high-entropy alloy FeCrCoMnNi by ultrasonic vibration-assisted diamond turning. Issue 1 (2021) - Zhang, Lin; Hashimoto, Takeshi; Yan, Jiwang
Abstract: High-entropy alloy (HEA) is an emerging alloy which consists of five or more metallic elements with equimolar concentrations and exhibits excellent mechanical properties at cryogenic temperature. However, its machinability is almost unknown. In this study, high frequency one-dimensional ultrasonic vibration-assisted diamond turning (UVDT) experiments were conducted on an FeCrCoMnNi-based HEA to investigate the micro-nanoscale material removal mechanisms. Compared with conventional diamond turning, UVDT produced thinner chips, lower cutting forces, less tool wear and better surface integrity. Due to the ultrasonic vibration-assisted burnishing effect, surface scratches were significantly eliminated. A freeform surface was test-fabricated with optical-level finish.